Differences in the ENAM grade and the university weighted average in applicants to the Peruvian Rural Health Service, 2008-2015 - Mendoza-Chuctaya, G. (2018)
Objective: To assess the prevalence of disrespect and abuse during childbirth and its associated factors in Peru. Methods: In an observational cross-sectional study, women were surveyed within 48 hours of live delivery at 14 hospitals located in nine Peruvian cities between April and July 2016. The survey was based on seven categories of disrespect and abuse proposed by Bowser and Hill. To evaluate factors associated with each category, prevalence ratios (PRs) and 95% confidence intervals (CIs) were calculated using adjusted Poisson models with robust variances. Results: Among 1528 participants, 1488 (97.4%) had experienced at least one category of disrespect and abuse. Frequency of abandonment of care was increased with cesarean delivery (PR 1.27, 95% CI 1.03–1.57) but decreased in the jungle region (PR 0.27, 0.14–0.53). Discrimination was associated with the jungle region (PR 5.67, 2.32–13.88). Physical abuse was less frequent with cesarean than vaginal delivery (PR 0.23, 0.11–0.49). The prevalences of abandonment of care (PR 0.42, 0.29–0.60), non-consented care (PR 0.70, 0.57–0.85), discrimination (PR 0.40, 0.19–0.85), and non-confidential care (PR 0.71, 0.55–0.93) were decreased among women who had been referred. Conclusion: Nearly all participants reported having experienced at least one category of disrespect and abuse during childbirth care, which was associated with type of delivery, being referred, and geographic region. © 2017 International Federation of Gynecology and Obstetrics.